The era of artificial intelligence in malaysian higher education: Three minutes exploration (3ME) with flexible approach path (FAP) for effective learning process in self exploration education system (SEES) - Muhamad Fazil, Ahmad (2018)
Artificial Intelligence (AI) is the creation of a smart machine that has human behavior and response. AI in the education sector is able to interact, assist, and guide students through Self-Exploration Education (SEE), such as current, but semi-automatic learning systems. Everyone is born as a genius, with curiosity to explore the environment through experiments. However, in practice, SEE is still very much focused on spreading facts rather than encouraging personal exploration. Conducting exploration of learning in the classroom can be complicated for adult learning or andragogy and is limited by virtue, money and work infrastructure. But what if we can create a middle ground between learning and fiction, the world in which adults learn and explore in ways that may be impossible in real life but still true to the transfer of knowledge? The project is to craft an imaginative and accessible tool to help adults develop scientific minds and practices through self-exploration or Do-it-yourself DIY with a mixed reality learning system that empowers adults to know the invisible and investigate hard through exploration. The system combines exploration and engagement technology with various traditional AV Audio mechanisms from flip cards, books and CDs to bring the living world. In such a way, adults can interact with real materials, books, to unlock tremendous virtual phenomena. They can discover things that are invisible to the naked eye through metaphorical materials. And they can also carry out experiments that are impossible in reality by creating their own universe and controlling parameters in the simulation. And the lively interaction raises their interest and enthusiasm for more technical exploration.